The human salivary microbiome exhibits temporal stability in bacterial diversity - Cameron, Simon J. S.; Huws, Sharon A.; Hegarty, Matthew J.; Smith, Daniel P. M.; Mur, Luis A. J. (FEMS microbiology ecology, 2015)
The temporal variability of the human microbiome may be an important factor in determining its relationship with health and disease. In this study, the saliva of 40 participants was collected every 2 months over a one-year period to determine the temporal variability of the human salivary microbiome. Salivary pH and 16S rRNA gene copy number were measured for all participants, with the microbiome of 10 participants assessed through 16S rRNA amplicon sequencing. In February 2013, 16S rRNA gene copy number was significantly (P < 0.001) higher, with individual changes between time points significant (P = 0.003). Salivary pH levels were significantly (P < 0.001) higher in December 2012 than in October 2012 and February 2013, with significant (P < 0.001) individual variations seen throughout. Bacterial α-diversity showed significant differences between participants (P < 0.001), but not sampling periods (P = 0.801), and a significant positive correlation with salivary pH (R2 = 7.8%; P = 0.019). At the phylum level, significant differences were evident between participants in the Actinobacteria (P < 0.001), Bacteroidetes (P < 0.001), Firmicutes (P = 0.008), Fusobacteria (P < 0.001), Proteobacteria (P < 0.001), Synergistetes (P < 0.001) and Spirochaetes (P = 0.003) phyla. This study charted the temporal variability of the salivary microbiome, suggesting that bacterial diversity is stable, but that 16S rRNA gene copy number may be subject to seasonal flux. This is the first study to chart the temporal variability of the salivary microbiome and suggested that this was stable in terms of its diversity but not load over a one-year period.